Kebijakan Pengembangan Koleksi Perpustakaan Universitas Islam Negeri Raden Fatah Palembang - Nurmalina Nurmalina (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Collection is one of the requirements for the formation of a library in addition to library staff, facilities and infrastructure, a source of funding. Library collections are tailored to the needs of visitors, library types, and agency policies. The university library must have an adequate collection of both the number of titles and the number of copies. The collection is sufficient to support the implementation of education, research, and community service. In order for the development of a focused collection, a collection development policy is needed. This research uses a descriptive qualitative approach. This approach is used to describe the collection development that has been carried out by the library of UIN Raden Fatah Palembang along with the obstacles faced, as well as to collect data to make a written collection development policy. Data collection was carried out through observation, interviews and documentation. The findings in this study are that so far the UPT Library of UIN Raden Fatah has only carried out collection development activities by practice, but there is no collection development policy that will be used as a guide in carrying out collection development activities. This is so that the implementation of collection development activities is not well directed, because there are no guidelines in carrying out collection development activities.